Clinical profile and quality of life in climacteric women - Cíntia Mikaelle Cunha de Santiago Nogueira; Bárbara Daniely dos Santos Silva; Hosana Mirelle Goes Silva Costa; Jussara Rodrigues de Alcantara; Fátima Raquel Rosado Morais; Renata Janice Morais Lima Ferreira Barros; Susy Maria Feitosa de Melo Rabelo; Emanuelly Vieira Pereira; José Rodolfo Lopes de Paiva Cavalcanti; Natália Teixeira Fernandes; Ana Virginia de Melo Fialho (BMC, 2022)
Abstract Background The Quality of Life in climacteric women is intrinsically related to signs and symptoms influenced by the decrease of estrogen and psychosocial factors linked to the natural aging process. Thus, this study aimed to trace the sociodemographic and clinical profiles of climacteric women working at the State University of Rio Grande do Norte (UERN) and evaluate their Quality of Life. Methods It is a descriptive, exploratory, and quantitative study. The population consisted of female workers from UERN, aging between 40 and 65 years. The total sample consisted of 63 women who answered the forms. Data collection was completely online, which allowed the women to have free choice to choose the most appropriate time to answer the questions. Results The majority of the participants were older than 50 years (53.97%, n = 34), were married or in a stable union (55.56%, n = 35), and lived in Mossoró-RN (82.53%, n = 52). Regarding skin color, white and brown women had the same percentage of 44.44% (n = 28). The pain, general health status, and vitality domains evidence the predominance of poor quality of life in the SF-36 questionnaire. Regarding the level of satisfaction with their current health status, 4.76% (n = 3) stated that they fit the level considered excellent, 44.44% (n = 28) very good, 46, 03% (n = 29) were good, and 4.77% (n = 3) stated unsatisfied with their current health status. The intensity of symptoms related to estrogen deficiency established by the Kupperman menopause index is as Mild 55.56% (n = 35), moderate 41.27% (n = 26), and severe 3.17% (n = 2). Conclusions The occurrence of symptoms and perception of these symptoms differs from woman to woman, to a greater or lesser extent. These findings emphasize the need for qualified and individualized care for the needs of these women in health services and the development of applicable solutions for solving problems based on each woman profile.